Realism in the Hebrew short story: Deborah Baron as a model - Emad saaed deabel, Prof. (lark, 2026)
My research, entitled "Realism in the Hebrew Short Story - Deborah Baron as a Model," examines the realism of Deborah Baron, a prominent writer in modern Hebrew literature and a master of the Hebrew short story. One critic remarked, "From now on, she will be considered one of the mothers of modern literature, just as the fathers of literature are." The research includes an introduction defining realism, its types, and its presence in modern Hebrew literature. It then provides an overview of the short story and its pioneers in European and modern Arabic literature, particularly Deborah Baron. Following this, the research presents a biography of the writer, her style, and the artistic structure of her stories. After this introduction, the research also includes three short sections discussing realism in the stories "Ash’a," "Shfara," and "Sumna."